Impact of oxygen atmosphere on piezoelectric properties of CaBi2Nb2O9 thin films - Simoes, A. Z.; Riccardi, C. S.; Cavalcante, L. S.; Longo, Elson [UNESP]; Varela, José Arana [UNESP]; Mizaikoff, B. (Elsevier B.V., 2007)
CaBi2Nb2O9 (CBNO) thin films were deposited on platinum-coated silicon substrates by the polymeric precursor method, and were annealed in air and in an oxygen atmosphere. The structure, surface morphology and electrical properties of CBNO thin films have been investigated. The presence of an oxygen atmosphere during crystallization of the films affected the structure perfection and morphology, as well as ferroelectric and piezoelectric properties. A reduction in P-r and piezoelectric coefficient, an increase of V-c and displacement of the Curie point is evident in the films crystallized in an oxygen atmosphere. The impact of exposure to the oxygen atmosphere on the creation of defects caused by bismuth and oxygen vacancies between layers was also investigated by X-ray photoelectron spectroscopy. (c) 2007 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: piezoelectricity; vacancies; point defects; CaBi2Nb2O9; x-ray photoelectron spectroscopy